STUDENTS’ AND ACADEMIC STAFFS’ PERSPECTIVES ON AN INTERPROFESSIONAL EDUCATION MODEL - Eti Poncorini Pamungkasari; Ari Probandari; Amandha Boy Timor Randita; Sri Anggarini Parwatiningsih (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Teamwork in health care is beneficial because it allows a holistic approach to patient care. Interprofessional education (IPE) provides students with an opportunity to develop their professional roles and their functions as team members. Understanding Interprofessional Collaboration (IPC) from the perspective of student and academic staff is an essential assessment for creating IPE model.Methods: This was a qualitative study with phenomenology approach. We explored students’and academic staff’s perspective of IPE by focus group discussions. We selected fifteen midwifery student, twenty medical students and twenty-two lecturers (midwifery and obstetrician gynecologist doctor) who were involved in IPE project. Data analysis used thematic analysis technique.Results: Findings showed four themes that presented the most common perspective in collaborative experience, (1) interprofessional communication, (2) the role each profession, (3) IPE learning model, and (4) suggested IPE model. The major obstacle was poor communication in daily practices. Developing an IPE model is important to improve patient care.Conclusion: The main common problem of IPC was interprofessional communication. That poor communication problem can be solved by developing intra-curricular and extra-curricular IPE model and train the effective interprofessional communication.